2019
DOI: 10.3389/fmats.2019.00185
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Corrosion-Resistant Coatings From Waterborne Polyurethane Modified Epoxy Emulsion

Abstract: Corrosion of metal products can seriously affect their reliability. The application of coatings is the most widely used method of corrosion protection due to the desire for easy application and low cost. Most of the present corrosion-resistant coatings are solvent coatings. Due to the high content of volatile organic compounds, the use of solvent coatings is restricted. Currently, the corrosion resistance of waterborne coatings is much lower than that of solvent coatings, so research and development of waterbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In Figure 2 , compared with curve a, the absorption peak at 829 cm −1 in curve b was attributed to the bending vibration generated by the replacement of two pairs of hydrogen atoms of the benzene ring in the epoxy resin [ 21 ]. Due to the ring-opening reaction of the epoxy group, no absorption peak of the epoxy group was observed at 910 cm −1 [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2 , compared with curve a, the absorption peak at 829 cm −1 in curve b was attributed to the bending vibration generated by the replacement of two pairs of hydrogen atoms of the benzene ring in the epoxy resin [ 21 ]. Due to the ring-opening reaction of the epoxy group, no absorption peak of the epoxy group was observed at 910 cm −1 [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, their capacity to increase the corrosion resistance of Mg alloy was assessed. Previous studies showed that certain types of PU coating can provide protection on Mg alloys from corrosion [78], yet did not present any effect of bacterial resistance. The acidic metabolites secreted/excreted by bacteria (depending on the strains) can cause further corrosion once these bacteria adhere to the surface [79].…”
Section: Effect Of Microstructures and Membrane Mechanisms On Antibac...mentioning
confidence: 94%
“…However, the antismudge property of coatings was unsatisfactory due to the low cross-linking degree and massive hydrophilic polar groups. To improve the antismudge property of coatings, a second component with a few functional reactive groups, such as hexamethoxymethylmelamine (HMMM) and hexamethylene diisocyanate trimer (HDIT), should be added additionally in the dispersion, prior to the coating forming stage, to ensure the hydrophilic polar groups are consumed during the coating curing process. , Although this method could obtain NP-GLIDE WPU coatings with antismudge property at a low PDMS content (1.0–5.0 wt %), the coating preparation process is complicated by adding the second reactive component to compensate for the lack of cross-linking degree to improve the water-resistance properties.…”
Section: Introductionmentioning
confidence: 99%